MODEL OF SNAKE LADDER GAME AGAINST SOCIAL VALUE OF SOCIETY THROUGH SOCIAL INTERACTION IN THE COVID 19 PANDEMIC - Pertiwi, Eky Prasetya; Dedy Ariyanto; Febrina Gerhani; Ianatuz Zahro (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2024)
This study aimed to know whether there is an interaction between the snake and ladder game model and the community social interaction. The type this research was quantitative method and the design used is the experimental method. The research was carried out at TK Labschool Jember and TK Aisyiyah Bustanul Athfal ( ABA) Kalisat. Based on the result of the research showed that there was no interaction between the snake and ladder game model and the community social interaction. H0 is rejected and Ha is accepted if Fhitung has a significance less than 0.05 (Sig < 0.05). H0 in this study means that there was no interaction between the snake and ladder game model and social interaction with the social values of the community. The results of the analysis found that there were factors that influenced no interaction between the snake and ladder game model and social interaction on the social values of the community, including too many children playing the snake and ladder game, lack of time for children because this activity was carried out for the first time in covid 19 era. This game played after the children did not meet face to face at school and even play activities with their peers in long time period, besides that children do not understand the meaning of social values in society.